3. Differential Diagnosis - Masumori, S.; Nogaki, M. (Nippon Daicho Komonbyo Gakkai Zasshi, 1980)
It is most important to know the etiology of fistula ani (for example, colitis ulcerosa, Crohn's disease, etc.) and to understand the pathogenesis. Once this is accomplished, it is easy to differentiate fistula ani from other diseases. The actual entity of fistula is distinguished by the presence of the primary opening, the sinus tract, and the secondary opening. The circumferential lesions have been organized into 5 groups such as perianal, anal canal, ischiorectal, intratectal, and presacral region. In the presacral region, there are three important factors that should be given careful clinical attention. The first is the presence of postanal sinus, or dimple, and abscess. The repeated anorectal surgery as a result of misdiagnosis may induce an anorectal functional insufficiency. The second factor is the 60-80% frequency of congenital lesions occuring in this region. Approximately one third of these lesions may be maliganant. The third, and final factor is the low incidence of such lesions. It has been reported for only one out of 40, 000 hospitalized patients and one out of 7, 000 cases examined rectosig-moidoscopially. Therefore, it can be seen from these point that the presacral region is most important to differentiate fistula ani. Generally, anorectal diagnosis can be made in over 90% of the cases on the digital examination, using careful and skillful techniques. Many other exami-nations (blood, x-ray, endoscopy, biopsy, angiography, etc) may also be performed, but, deter-mined diagnosis should be performed histopathologically. However, we propopsed the necessity of recto-, and anorectal digital examination.